Rohingya refugees : Turks to the rescue - Farish A. Noor (2015)
Turkey’s decision to send a ship to rescue Rohingya at sea is another instance of Turkish soft power at work. Turkey has been playing an increasingly visible role in relief operations in other parts of the world, projecting itself as a benevolent Muslim power and earning the trust of non-Turkish Muslim communities.